Serum Inflammatory Markers and Histopathological Findings in Patients with Community-Acquired Acute Viral Hepatitis - Muhammad Sadiq, Abdul Ahad Mehboob, Hassan Raza Heral, Santosh Kumar Sidhwani, Muhammad Kaleem, Hussain Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Community-acquired acute viral hepatitis (CA-AVH) remains a significant public health challenge in Pakistan, with hepatitis A, B, C, and E viruses contributing to substantial morbidity. While histopathology remains the gold standard for assessing hepatic injury, invasive procedures are often limited in acute cases. Serum inflammatory markers may serve as valuable non-invasive surrogates that reflect underlying tissue-level damage. Objective: To evaluate the relationship between serum inflammatory markers and histopathological findings in patients with CA-AVH. Methods: A cross-sectional observational study was conducted at Khyber Teaching Hospital (KTH), Peshawar, Pakistan, from January 2022 to February 2023. A total of 100 patients aged 18–60 years with serologically confirmed CA-AVH were enrolled. Clinical and biochemical profiles were recorded, and serum inflammatory markers including C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were measured using standard assays. Liver biopsies were performed in 30 patients with prolonged jaundice or uncertain diagnosis and were graded for necroinflammatory activity using the modified Knodell scoring system. Statistical analyses included Student’s t-test, ANOVA, and Pearson’s correlation coefficient. Results: The mean age of patients was 33.2 ± 8.9 years, with a male predominance (62%). The distribution of viral etiology was HAV (18%), HBV (32%), HCV (12%), and HEV (38%). Elevated CRP was observed in 68% of patients, while IL-6 and TNF-α levels were significantly higher in HBV and HEV infections. Histopathological features included portal inflammation (80%), hepatocyte ballooning (73%), lobular necrosis (63%), and interface hepatitis (40%). CRP correlated strongly with lobular necrosis (r = 0.62, p < 0.01), IL-6 with portal inflammation (r = 0.71, p < 0.01), and TNF-α with ballooning degeneration and interface hepatitis (r = 0.68, p < 0.01). Conclusion: Serum inflammatory markers reflect the severity of histopathological injury in CA-AVH. IL-6 and TNF-α, in particular, show strong correlations with necroinflammatory activity and may serve as reliable non-invasive indicators of disease severity, thereby reducing reliance on liver biopsy in resource-limited settings. Keywords: Acute viral hepatitis, community-acquired infection, inflammatory markers, IL-6, TNF-α, histopathology, liver biopsy, Pakistan.